Dietary inclusion of probiotics and a prebiotic improved the health and performance of broilers challenged with Salmonella Typhimurium - Van Rensburg, Connie E.J. (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2011.